Phytochemical and pharmacological investigations of different extracts of leaves and stem barks of Macropanax dispermus (Araliaceae): a promising ethnomedicinal plant - Syeda Rubaiya Afrin; Mohammad Rashedul Islam; Bibi Humayra Khanam; Nawreen Monir Proma; Sayeda Saima Didari; Sarah Waddun Jannat; Mohammed Kamrul Hossain (SpringerOpen, 2021)
Abstract Background Macropanax dispermus is traditionally used to treat various diseases by ethnic people. The present research reports the pharmacological properties with phytochemical profiling of the crude extracts of M. dispermus leaves (MDML), its n-hexane (MDHL), carbon tetrachloride (MDTL), chloroform (MDCL), ethyl acetate (MDEL), and aqueous (MDAL) fractions, and crude methanol extracts of its stem barks (MDMS). The in vitro thrombolytic activity was done on human erythrocytes whereas the cytotoxic activity was done by brine shrimp lethality assay. The in vivo analgesic activity was examined by acetic acid-induced writhing, tail immersion, and formalin-induced paw licking method. In contrast, antipyretic activity was done by the brewer's yeast-induced pyrexia method. Results MDHL and MDMS showed 37.05% and 42.21% of significant (p < 0.01) thrombolytic activity, respectively. MDCL and MDMS showed the lower LC50 values of 23.15 and 37.11 µg/ml during cytotoxicity test, respectively. In acetic acid writhing method, MDTL and MDEL showed significant (p < 0.001) inhibition of writhing by 79.34% and 80.17%, respectively. MDMS showed significant (p < 0.001) maximal possible effect (%MPE) of 45.95%, 62.26%, 65.79%, 89.69% and elongation of time in pain reaction of 48.53%, 60.28%, 58.76%, and 70.14% at 30, 60, 90, and 120 min intervals, respectively. MDML at 400 mg/kg exhibited significant (p < 0.001) 82.72% of inhibition of pain at the late phases. MDEL at 400 mg/kg of dose exhibited significant (p < 0.001) reduction of rectal temperature by 36.31%, 62.42%, 89.81%,, and 96.82% at 1, 2, 3, and 4 h intervals, respectively. Conclusion The current research suggests that the plant extracts possess potential thrombolytic, cytotoxic, analgesic, and antipyretic activities.